"A Foras, Out": Youth antimilitarism engagement in Sardinia. (1st January 2020) - Esu, Aide
Abstract : This paper presents a short review of the A Foras, Out movement in Sardinia and examines its youth branch, the student collective ( Collettivo studentesco ) for university and high school students. Since the late 1960s, grassroots movements, associations, committees, political groups, antimilitarists and ecologists have struggled against land occupation by NATO and other military forces and called for the drastic reduction or elimination of military activities on the island that was later related to the emergence of environmental risk and diseases. By participating in networked collective actions, these young activists reclaim the land occupied by the military and elaborate a legitimisation-based political rhetoric that undermines the legality of the presence of military bases in Sardinia. The young activists emerge as social actors in engaging debates within the movement about of civil disobedience practices that sometimes cross the boundary of illegal practices (e.g. cutting fences around military areas to stop training). Their engagement pushes the actions of the senior non-violent antimilitarist activists into a new, not yet defined practice of antimilitarism incorporating diverse political platforms: from independence movements to traditional workerism, anarchists to radical left-wing movements. We analyse the youth group's agency in transforming antimilitarism from general pacifism into a mixed antimilitarist-eco, neo-independence movement calling for new regional sovereignty.